Naming the genus Marivivens and its species: etymological considerations - Oren, Aharon; Kostovski, Marko; Schink, Bernhard; Ventura, Stefano (Microbiology Society, 2025)
The name Marivivens marinum, published as sp. nov. by Kang et al. (Int J Syst Evol Microbiol 2025;75 : 006735) contravenes Rule 12 c(1) of the International Code of Nomenclature of Prokaryotes (ICNP). Albeit the authors of the genus name Marivivens Park et al. 2016 did not specify the gender of the name, the epithet donghaensis of the type species was given the masculine gender, and so was the epithet of Marivivens geojensis (Lee et al. 2019) Qu et al. 2022. Therefore, we here correct the name Marivivens marinum to Marivivens marinus corrig. We also give examples of the correct use of present participles as genus names, based on the rules of the ICNP and on past usage in the nomenclature of prokaryotes.
Keywords: adjectives; gender; Marivivens; nomenclature; participles